2018
DOI: 10.1088/1748-9326/aadcb2
|View full text |Cite
|
Sign up to set email alerts
|

Drop-in biofuels offer strategies for meeting California’s 2030 climate mandate

Abstract: In 2015, California established a mandate that requires on-road greenhouse gas (GHG) emissions to be reduced by 40% below 1990 levels by 2030. We explore the feasibility of meeting this goal by largescale commercialization of drop-in biofuels. Drop-in biofuels, although not clearly defined, are a class of fuels that can be produced from biomass and blended with either crude oil or finished fuels without requiring equipment retrofits. This article focuses on thermochemical routes at or near commercialization. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the pursuit of low-carbon logistics, in addition to direct carbon emission factors, biofuels and transportation technologies are crucial for emission reduction [40,41]. Additionally, electric vehicles (EVs) are widely considered as they can reduce the dependence on fossil fuels and contribute to the low-carbon circular economy [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…In the pursuit of low-carbon logistics, in addition to direct carbon emission factors, biofuels and transportation technologies are crucial for emission reduction [40,41]. Additionally, electric vehicles (EVs) are widely considered as they can reduce the dependence on fossil fuels and contribute to the low-carbon circular economy [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Biological carbon sources have three critical roles to play in reaching global climate change mitigation goals: providing energy-dense fuels for difficult-to-electrify transportation modes, enabling net carbon-negative technologies at lower costs than what is achievable with direct air capture, and replacing petrochemicals with bio-based alternatives. , However, the bioeconomy has fallen short of achieving these goals to date. The Energy Independence and Security Act of 2007 set a U.S. cellulosic fuel production target of 16 billion gallons by 2022, but this goal was revised to just 0.63 billion gallons in the latest final volume requirements. , This shortfall stems from a variety of factors, including blend wall limitations for ethanol, fluctuating crude oil prices, and challenging economics for the conversion of lignocellulosic material to advanced liquid fuels. , The narrow aim of producing a single liquid biofuel as cheaply as possible overlooks the range of services biorefineries can provide. Commercial-scale cellulosic biorefineries have the potential to play a multifaceted role in the future carbon economy by serving as both fuel production and waste treatment infrastructure, ultimately producing multiple fuel and non-fuel products.…”
Section: Introductionmentioning
confidence: 99%
“…3 , 4 This shortfall stems from a variety of factors, including blend wall limitations for ethanol, fluctuating crude oil prices, and challenging economics for the conversion of lignocellulosic material to advanced liquid fuels. 5 , 6 The narrow aim of producing a single liquid biofuel as cheaply as possible overlooks the range of services biorefineries can provide. Commercial-scale cellulosic biorefineries have the potential to play a multifaceted role in the future carbon economy by serving as both fuel production and waste treatment infrastructure, ultimately producing multiple fuel and non-fuel products.…”
Section: Introductionmentioning
confidence: 99%
“…Lignocellulosic bioenergy crops have the advantage of being renewable energy resources with reduced carbon emissions compared to petroleum-based fuel. Recent studies have demonstrated that the use of lignocellulosic biofuels has the potential to sequester carbon from the atmosphere by increasing soil organic carbon, which may help mitigate increased carbon release to the atmosphere ( Vanholme et al, 2013 ; Taptich et al, 2018 ; Wu et al, 2018 ). Despite these advantages, lignocellulosic biofuels have several requirements to meet before they can be considered competitive with petroleum-based fuels.…”
Section: Introductionmentioning
confidence: 99%